2009
DOI: 10.2134/jeq2008.0350
|View full text |Cite
|
Sign up to set email alerts
|

Streamside Management Zones Effectiveness for Protecting Water Quality after Forestland Application of Biosolids

Abstract: Biosolids, materials resulting from domestic sewage treatment, are surface applied to forest soils to increase phosphorus (P), nitrate, and ammonium availability. Retaining streamside management zones (SMZs) can limit nutrient pollution of streams. We delineated 15-m SMZs along three intermittent streams in an 18-yr-old Pinus taeda L. plantation. We applied biosolids at a rate of 1120 and 629 kg ha(-1) of total nitrogen and total P outside the SMZ on one side of each of the streams while maintaining the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…These values are higher than the total N removal levels of 60 -80 found in the Allegheny Plateau (Kochenderfer and Hornbeck 1999) and Cumberland Plateau (Arthur et al 1998) and are six times higher than those reported by Wynn et al (2000) for the Coastal Plain. The higher NO 3 Ϫ removal efficiencies found in this study are suspected to be partially caused by the dry conditions, but Pratt and Fox (2009) also found Ն90% NO 3 Ϫ removal efficiencies from subsurface water in SMZs located adjacent to biosolid applications in the Virginia Piedmont. NH 4 ϩ removals between the fertilized stands and stream edge ranged from 68.7 to 92.8 in surface waters and 87 to 97.4 for near-surface waters (Table 6).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…These values are higher than the total N removal levels of 60 -80 found in the Allegheny Plateau (Kochenderfer and Hornbeck 1999) and Cumberland Plateau (Arthur et al 1998) and are six times higher than those reported by Wynn et al (2000) for the Coastal Plain. The higher NO 3 Ϫ removal efficiencies found in this study are suspected to be partially caused by the dry conditions, but Pratt and Fox (2009) also found Ն90% NO 3 Ϫ removal efficiencies from subsurface water in SMZs located adjacent to biosolid applications in the Virginia Piedmont. NH 4 ϩ removals between the fertilized stands and stream edge ranged from 68.7 to 92.8 in surface waters and 87 to 97.4 for near-surface waters (Table 6).…”
Section: Resultssupporting
confidence: 53%
“…Their nutrient analyses were based on limited samples, because of drought conditions, but the authors speculated that the 15-m SMZ, with or without harvest, appeared to be sufficient for minimizing NO 3 Ϫ and P movement to the stream. Pratt and Fox (2009) evaluated the effectiveness of 15.2-m-wide SMZs for minimizing movement of N and P to streams after applications of biosolids in the Virginia Piedmont. The biosolids were applied to an 18-year-old loblolly pine plantation at rates of 1,120 kg ha Ϫ1 for N and 629 kg ha Ϫ1 for P. After 1 year of monitoring, their results indicated that the 15.2-m buffer was adequate for nonpoint source pollution protection, although they did find one period of elevated stream P after overland flow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wood ash, created during wood combustion for energy, can be safely used to replace calcium and other basic cations removed through biomass harvesting (Pitman, 2006). Concerns related to the impact of forest fertilization on water quality have generally been unfounded (Binkley et al, 1999), even in intensively managed systems (McBroom et al, 2008) or when biosolids are applied (Pratt and Fox, 2009). …”
Section: Sustainability Of Extracting Primary Forest Residue Biomassmentioning
confidence: 99%
“…Forest land application, rather than applying biosolids to agricultural land, can reduce the risk of contaminants entering the human food chain [8]. In addition, forest application can increase tree growth and subsequent economic returns [9], [10], [11], [12]. However, few studies have been conducted to quantify the economic return of forests associated with land application of biosolids.…”
Section: Introductionmentioning
confidence: 99%